Trait emotional intelligence and foreign language performance: associations with academic self-efficacy and foreign language anxiety - Jin, Feiyang; Gu, Chufeng; Li, Yu (Frontiers in Education, 2024)
Recent years have witnessed extensive research examining the influences of positive psychological factors in foreign language learning. Building on these endeavors, the current study was specifically designed to examine how positive psychological factors including trait emotional intelligence (TEI), academic self-efficacy, and foreign language anxiety (FLA) exert influences on foreign language performance in college students who are learning a foreign language. To this end, 203 Chinese college students (141 women), recruited through snowball sampling, completed three validated questionnaires to measure their TEI (Trait Emotional Intelligence Questionnaire - Short Form), academic self-efficacy (the Chinese version of the Academic Self-Efficacy Questionnaire), and FLA levels (the Chinese version of Foreign Language Classroom Anxiety Scale). Additionally, an in-house self-rating questionnaire assessed their self-perceived foreign language performance. Mediation analysis was used to determine whether and how academic self-efficacy and FLA levels contribute separately and interactively to the relationship between TEI and foreign language performance. The results showed that: (a) there were moderate to strong associations between TEI, academic self-efficacy, FLA levels, and self-perceived foreign language performance; and (b) academic self-efficacy and FLA levels played separate and sequential mediating roles between TEI and self-perceived foreign language performance. Together, these findings highlight how TEI, academic self-efficacy, and FLA levels contribute to foreign language performance in college students. They also suggest the potential application of these positive psychological factors in mitigating anxiety elicited by learning a foreign language and improving language performance.